Comparative analysis of fungal communities between herbicide-resistant and -susceptible Alopecurus aequalis - Zhan, You; Liu, Haozhe; Cao, Ziheng; Chen, Wen; Li, Zongfang; Bai, Lianyang; Pan, Lang (Frontiers in Cellular and Infection Microbiology, 2022)
Alopecurus aequalis is a grass species invading Chinese canola and wheat fields. An A. aequalis population KMN-R surviving from mesosulfuron-methyl treatment with recommended rates was acquired from wheatland. Here we aimed to confirm resistance profiles of KMN-R to acetolactate synthetase (ALS) inhibiting herbicides and study mesosulfuron-methyl resistance mechanisms in this population. Dose response results indicated that KMN-R population evolved resistance to mesosulfuron-methyl and other tested ALS-inhibiting herbicides. Known resistance-conferring Trp-574-Leu gene mutation in A. aequalis ALS was detected in KMN-R population. Pre-treatment with 4-chloro-7-nitrobenzoxadiazole reversed mesosulfuron-methyl resistance in KMN-R. Glutathione S-transferases (GST) gene GSTZ2 and GSTT3 were highly expressed in KMN-R population. In addition, we evaluated the alpha diversity in A. aequalis, centering on OTU abundance, equality, and multiplicity, and found fungal community composition had more unexplained variance between KMN-R and KMN-S A. aequalis. We also observed higher abundances of specific fungi in KMN-R A. aequalis. The results proved that resistance to mesosulfuron-methyl in KMN-R is probably caused by target-site and non-target-site based relating GST, and provided basis on further research between fungi interaction and herbicide resistance.